Barriers and facilitators to access mental health services among refugee women in high-income countries: a systematic review - DeSa, Sarah; Gebremeskel, Akalewold T.; Omonaiye, Olumuyiwa; Yaya, Sanni (Université d'Ottawa | University of Ottawa, 2022)
Abstract Background Based on the Global Trends report from the United Nations High Commissioner for Refugee, in high-income countries, there are 2.7 refuges per 1000 national population, girls and women account for nearly 50% of this refuge population. In these high-income countries, compared with the general population refuge women have higher prevalence of mental illness. Thus, this review was conducted to examine the barriers to and facilitators of access to mental health services for refugee women in high-income countries for refugee resettlement. Methods We searched MEDLINE, EMBASE, PsycINFO, and CINAHL databases for research articles written in English with qualitative component. The last search date was on March 14, 2020. A narrative synthesis was conducted to gather key synthesis evidence. Refugee women (aged 18 and older) that could receive mental health services were included. Men and women under non-refugee migrant legal status were excluded. Studies were evaluated studies using the Critical Appraisal Skills Programme (CASP) qualitative checklist. Results Of the four databases searched, 1258 studies were identified with 12 meeting the inclusion criteria. Three studies were cross-sectional by design, eight studies used a qualitative approach and one studies used mixed approach. The major barriers identified were language barriers, stigmatization, and the need for culturally sensitive practices to encourage accessing mental health care within a religious and cultural context. There were several studies that indicated how gender roles and biological factors played a role in challenges relating to accessing mental health services. The major facilitators identified were service availability and awareness in resettlement countries, social support, and the resilience of refugee women to gain access to mental health services. Conclusion This review revealed that socio-economic factors contributed to barriers and facilitators to accessing mental health among women refugees and asylum seekers. Addressing those social determinants of health can reduce barriers and enhance facilitators of access to mental health care for vulnerable populations like refugee women. A key limitation of the evidence in this review is that some data may be underreported or misreported due to the sensitive and highly stigmatizing nature of mental health issues among refugee populations. Systematic review registration PROSPERO CRD42020180369